Comparative physiology of allopatric Populus species: geographic clines in photosynthesis, height growth, and carbon isotope discrimination in common gardens - Soolanayakanahally, Raju Y.; Guy, Robert D.; Street, Nathaniel R.; Robinson, Kathryn M.; Silim, Salim N.; Albrectsen, Benedicte R.; Jansson, Stefan (Frontiers in Plant Science, 2015)
Populus species with wide geographic ranges display strong adaptation to local environments. We studied the clinal patterns in phenology and ecophysiology in allopatric Populus species adapted to similar environments on different continents under common garden settings. As a result of climatic adaptation, both Populus tremula L. and Populus balsamifera L. display latitudinal clines in photosynthetic rates (A), whereby high-latitude trees of P. tremula had higher A compared to low-latitude trees and nearly so in P. balsamifera (p = 0.06). Stomatal conductance (gs) and chlorophyll content index (CCI) follow similar latitudinal trends. However, foliar nitrogen was positively correlated with latitude in P. balsamifera and negatively correlated in P. tremula. No significant trends in carbon isotope composition of the leaf tissue (δ13C) were observed for both species; but, intrinsic water-use efficiency (WUEi) was negatively correlated with the latitude of origin in P. balsamifera. In spite of intrinsically higher A, high-latitude trees in both common gardens accomplished less height gain as a result of early bud set. Thus, shoot biomass was determined by height elongation duration (HED), which was well approximated by the number of days available for free growth between bud flush and bud set. We highlight the shortcoming of unreplicated outdoor common gardens for tree improvement and the crucial role of photoperiod in limiting height growth, further complicating interpretation of other secondary effects.